Incerta glòria di Joan Sales tra filología, storia e traduzione. - RlGOBON, PATRIZIO (Scripta, 2015)
This article makes a reflection on the work of Joan Sales, Incerta gloria, and it particularly affects the connection between philology, history and translation.